Corrigendum to “Multidrug resistance from a one health perspective in Ethiopia: a systematic review and meta-analysis of literatures (2015–2020)” [One Health 14(2022) 1–12/100390] - Mebrahtu Teweldemedhin; Saravanan Muthupandian; Tsega Kahsay Gebremeskel; Kibriti Mehari; Getahun Kahsay Abay; Teklay Gebrecherkos Teklu; Ranjithkumar Dhandapani; Ragul Paramasivam; Tsehaye Asmelash (One Health)
Purpose: The emergence of antimicrobial resistance is a major global health challenge and becoming an urgent priority of policymakers. There is a paucity of scientific studies presenting the multidrug resistance pattern from one health perspective in Ethiopia. Therefore, a systematic review and meta-analysis aimed to determine the pooled prevalence of multidrug resistance in bacteria from human, animal, food and environmental sources. Methods: In this systematic review and meta-analysis, an electronic search was made in PubMed &Google scholar using different keywords. The studies conducted in all areas of Ethiopia, published from 2015 to 2020 in the peer-reviewed journals, English full-length papers were included. The meta-analysis was done on STATA version 14. The pooled prevalence of multidrug resistance for each bacterium was analyzed using the random effects model; Cochran Q statistics and the I2 statistic was used to analyze heterogeneity and considered significant at p < 0.01. Results: A total of 81 studies were included in the systematic review and meta-analysis; 53 human studies, 8 animal studies and 16 environment/food studies. A total of 6 species from gram positive bacteria and 13 species from gram negative bacteria were included in the meta-analysis. S.aureus 53 % (95 %CI: 42–64 %), CoNS 68 %(95 %CI:53–82), Pseudomonas spp. 73 % (95 %CI:48–93 %), E. coli 70 % (95 %CI:61–78 %), Citrobacter spp. 71 % (95 %CI:54–87 %), Klebsiella spp. 68 % (54–80 %), Enterobacter spp. 67 % (48–83 %) and Salmonella spp. 65 % (95 %CI:48–81 %) were the common multi-drug resistant species of bacteria from the perspective of two or more sources. Conclusion: In Ethiopia, the pooled prevalence of MDR is high in most of the bacterial species from humans, animals, food and environmental sources. Staphylococcus species, most members of the Enterobacteriaceae and Pseudomonas species are the standard MDR bacterial populations involving all sources. Therefore, integrated policy and intervention measures should be implemented to reduce the emergence and spread MDR bacteria for better animal and human health outcomes.